The Impact of Macroeconomic Factors on Banks Liquidity Risk: Evidence From Pakistan - Muhammad Yar Khan; Javaria Liaqat; Tahira Awan; Wajid Khan (Journal of Business & Tourism, 2021)
The aim of the study is to identify the factors that influence liquidity risks of the banks by considering the panel of 18 top listed banks in Pakistan during a period of 2010 -2016. The study employed panel random effect regression model to absorb time-invariant shocks, which gives robust inferences. The results of liquidity risk confirmed that the country’s economic growth and price inflation further escalates liquidly risk while, FDI inflows reduces liquidity risks in Pakistani’s banks, thus it is concluded that bank’s liquidity risks required easy monetary policy to advancing loans and charging low interest rate, which ultimately will increase ROA, and ROE, while it would helpful to decrease high risk of bank’s liquidly in a given country.